Indicators of Body Reserve Opportunities for Young Gymnasts as One of the Factors for Successful Development of Initial Specialized Training - Zinaida Kuznetsova; Ilshat Dauletshin; Stanislav Kuznetsov (Lithuanian Sports University, 2018)
Background. The article deals with the problem of selection in gymnastics and the reasons why it is necessary to research that. Artistic gymnastics carries the heaviest losses on the initial stages of specialized training, which explains the lack of science-based regulatory requirements in the gymnastics system, allowing diagnosing, assessing and predicting the development of the main indicators of physical condition and fitness of athletes in complex. Research aim was to develop additional criteria of young gymnasts' selection at the initial stage of specialized training on the basis of the indicators of human body reserve opportunities. Methods. Experimental work was carried out with gymnasts aged 9 years (n = 15) and 10 years (n = 16) in the research laboratory of Povolzhskaya State Academy of Physical Culture, Sport and Tourism and sports complex "Yar Chally" in Naberezhnye Chelny, Republic of Tatarstan (Russia). Results. Gymnasts aged 9-10 years had a harmonious type of power supply of the body: more gymnasts had aerobic-anaerobic type of muscular activity power supply. Gymnasts who qualified in the obligatory program of category 3 on pommel horse equally represented only the second and the third biological groups. The results of correlation analysis suggest that for gymnasts aged 9 years, the most significant factors affecting their special physical and technical fitness included aerobic capacity source of muscle activity energy supply and general metabolic capacity and for gymnasts aged 10 years - capacity and anaerobic power glycolytic sources of energy and muscular activity. Discussion and conclusions. Obtained information on the preferred for gymnastics bioenergy groups can help coaches in predicting abilities of young gymnasts. Keywords:  sportspeople, gymnasts, selection, model descriptions, indicators of reserve opportunities.